INFLUENCIA DE LA DESHIDRATACIÓN AGUDA SOBRE EL COMPORTAMIENTO DE LA FRECUENCIA CARDIACA, EL CONSUMO DE OXÍGENO, EL LACTATO SANGUÍNEO Y EL PESO CORPORAL EN CORREDORES DE FONDO - Caldas Z, Rafael (Educación Física y Deporte, 2010)
With the purpose to determine differences among the heart rate (HR), plasmatic lactate (LAC) and oxygen consumption (V02) during a period of 90 minutes of running on a motorized treadmill (Quinton 1486) at 9,5 mph of speed and 1 % constant slope under conditions of hydration (H YD) and dehydration (DH YD), seven long distance male runners were studied. The laboratory conditions were 25 Celsius degrees, 65 % relative humidity and 1500 m above sea level. Each athlete were weighted at the beginning and at the finish of the running period. The first trial was made without drinking any kind of beverage and the second trial, seven days later, was made by drinking 150 ml of water each 15 minutes. Blood samples were withdrawn from the earlobe to determine LAC and the HR and VO2. (Ergooxiscreen Jaeger) were registered simultaneously. The results indicated a significative difference between HYD and NHYD treatments specially in LAC and HR. These parameters were higher in NHYD in a progressive way approximately increasing from minute 30. VO2 did not change significatively. Body weight deficit were higher in NHYD ranging from 1,7 to 3,9 % and HYD registered a lower déficit (0,5 to 2,4 %). The variation coefficients indicated a wide individual variation confirming previous reponed results. Also a negati ve influence of dehydration status on phy sical performance is demostrated but depending on a wide range on individual variations.